Takhrij and Syarah Hadith of Chemistry: Revealing the Secret of the Olive Fruit from the Hadith Instructions and Scientific Explanations - Riska Ardianna Putri; Dzikriyatun Qolbi Hizbullah; Yayan Mulyana; Muhtar Gojali; Nurhidayati Amaliah (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet. about the Olive plant. This research method is qualitative through the takhrij and sharah hadith approaches with chemical analysis. The result and discussion of this research is that the olive plant was popular at the time of the Prophet, and is known in the world of modern medicine, and has been proven through medical research. The conclusion of this research is takhrij and syarah hadith of the Prophet. about the Olive plant with chemical analysis which has various good benefits.